New regulators of Drosophila eye development identified from temporal transcriptome changes. Issue 4 (23rd January 2021) - Quiquand, Manon; Rimesso, Gerard; Qiao, Nan; Suo, Shengbao; Zhao, Chunyu; Slattery, Matthew; White, Kevin P; Han, Jackie J; Baker, Nicholas E
Abstract: In the last larval instar, uncommitted progenitor cells in the Drosophila eye primordium start to adopt individual retinal cell fates, arrest their growth and proliferation, and initiate terminal differentiation into photoreceptor neurons and other retinal cell types. To explore the regulation of these processes, we have performed mRNA-Seq studies of the larval eye and antennal primordial at multiple developmental stages. A total of 10, 893 fly genes were expressed during these stages and could be adaptively clustered into gene groups, some of whose expression increases or decreases in parallel with the cessation of proliferation and onset of differentiation. Using in situ hybridization of a sample of 98 genes to verify spatial and temporal expression patterns, we estimate that 534 genes or more are transcriptionally upregulated during retinal differentiation, and 1367 or more downregulated as progenitor cells differentiate. Each group of co-expressed genes is enriched for regulatory motifs recognized by co-expressed transcription factors, suggesting that they represent coherent transcriptional regulatory programs. Using available mutant strains, we describe novel roles for the transcription factors SoxNeuro (SoxN), H6-like homeobox (Hmx), CG10253, without children (woc), Structure specific recognition protein (Ssrp), and multisex combs (mxc).